The Role of Noncoding RNAs in Double-Strand Break Repair - Durut, Nathalie; Mittelsten Scheid, Ortrun (Frontiers in Plant Science, 2019)
Genome stability is constantly threatened by DNA lesions generated by different environmental factors as well as endogenous processes. If not properly and timely repaired, damaged DNA can lead to mutations or chromosomal rearrangements, well-known reasons for genetic diseases or cancer in mammals, or growth abnormalities and/or sterility in plants. To prevent deleterious consequences of DNA damage, a sophisticated system termed DNA Damage Response (DDR) detects DNA lesions and initiates DNA repair processes. In addition to many well-studied canonical proteins involved in this process, non-coding RNA (ncRNA) molecules have recently been discovered as important regulators of the DDR pathway, extending the broad functional repertoire of ncRNAs to the maintenance of genome stability. These ncRNAs are mainly connected with double strand breaks (DSBs), the most dangerous type of DNA lesions. The possibility to intentionally generate site-specific DSBs in the genome with endonucleases constitutes a powerful tool to study, in vivo, how DSBs are processed and how ncRNAs participate in this crucial event. In this review, we will summarize studies reporting the different roles of ncRNAs in DSB repair and discuss how genome editing approaches, especially CRISPR/Cas systems, can assist DNA repair studies. We will summarize knowledge concerning the functional significance of ncRNAs in DNA repair and their contribution to genome stability and integrity, with a focus on plants.